Eksistensi Hubungan Industrial Pancasila Pasca Disahkannya Peraturan Pemerintah Pengganti Undang-Undang Cipta Kerja - Dede Agus (Jurnal Ius Constituendum, 2023)
This study aims to examine the existence of Pancasila industrial relations after the enactment of the Job Creation Perppu. The urgency of this research is the ratification of the Job Creation Perppu which is substantively a continuation of the Job Creation Law which needs to be analyzed aspects of Pancasila industrial relations. This research is a normative legal research by prioritizing historical approaches, conceptual approaches, and statutory approaches. The results of the study confirm that Pancasila industrial relations as a base value in labor law, Pancasila values become a guide and guide in relations between workers and employers, including: (i) the formation of legal relations between workers and employers, (ii) the implementation of legal relations between workers and employers, (iii) legal guarantees in the form of proportional rights and obligations between workers and employers, and (iv) appropriate dispute resolution between workers and employers. Apart from that, after the ratification of the Job Creation Perppu, Pancasila industrial relations have not been formally regulated in the Job Creation Perppu. Apart from having implications for legal certainty regarding the conception of Pancasila industrial relations, the non-regulation of Pancasila industrial relations in the Perppu Cipta also has an impact on the existence of the Pancasila industrial relations concept which has the potential not to be implemented. The novelty of this research is that even though it is not regulated in the Job Creation Perppu, regulations concerning Pancasila industrial relations need to be regulated in statutory regulations, in particular through a Presidential Decree to ensure legal certainty on the conception of Pancasila industrial relations.Penelitian ini bertujuan mengkaji eksistensi hubungan industrial Pancasila pasca disahkannya Perppu Cipta Kerja. Urgensi penelitian ini adalah disahkannya Perppu Cipta Kerja yang secara substantif merupakan kelanjutan dari UU Cipta Kerja yang perlu dianalisis aspek hubungan industrial Pancasila. Penelitian ini merupakan penelitian hukum normatif dengan mengedepankan pendekatan kesejarahan, pendekatan konsep, dan pendekatan perundang-undangan. Hasil penelitian menegaskan bahwa hubungan industrial Pancasila sebagai base value dalam hukum ketenagakerjaan maka nilai-nilai Pancasila menjadi pemandu dan penuntun dalam relasi antara pekerja dan pengusaha, meliputi: (i) pembentukan hubungan hukum antara pekerja dan pengusaha, (ii) pelaksanaan hubungan hukum antara pekerja dan pengusaha, (iii) jaminan hukum berupa hak dan kewajiban yang proporsional antara pekerja dan pengusaha, serta (iv) penyelesaian sengketa secara patut antara pekerja dan pengusaha. Selain itu, hubungan industrial Pancasila pasca disahkannya Perppu Cipta Kerja secara formal belum diatur dalam Perppu Cipta Kerja. Selain berimplikasi pada kepastian hukum mengenai konsepsi hubungan industrial Pancasila, tidak diaturnya hubungan industrial Pancasila dalam Perppu Cipta juga berdampak pada eksistensi konsepsi hubungan industrial Pancasila yang berpotensi tidak diterapkan. Kebaruan penelitian ini yaitu sekalipun tidak diatur dalam Perppu Cipta Kerja, pengaturan mengenai hubungan industrial Pancasila perlu diatur dalam peraturan perundang-undangan, khususnya melalui Perpres untuk menjamin kepastian hukum pada konsepsi hubungan industrial Pancasila.